Analysis of the underlying mechanism of Ziziphi Spinosae Semen for treating anxiety disorder in a zebrafish sleep deprivation model - Jian Zhang; Junli Feng; Chenyu Feng (Pharmaceutical Science Advances)
Anxiety and depression are the most prevalent psychiatric disorders in the world, and they are highly comorbid with each other. Ziziphi Spinosae Semen (ZSS) is a traditional Chinese herbal medicine widely used in the treatment of insomnia and anxiety in clinical practice. To explore the effects of ZSS in alleviating anxiety in a sleep deprivation (SD) zebrafish model, the locomotor activity performance and anxiety behavior of these experimental fish were evaluated, and the underlying mechanisms of its anti-anxiety effect were examined by analyzing the transcriptomics of brain tissues. Results indicated that ZSS could significantly reduce the freezing duration and alleviate anxiety-like behavior. Moreover, ZSS was effective in promoting melatonin biosynthesis and synaptic transmission, modulating circadian rhythm, and preventing inflammatory response and oxidative stress, as evidenced by the expression alterations of the key anti-oxidation genes (GCLC, GPX1A, GSR, NRF2A and PRDX1) and pro-inflammatory cytokine (IL2RGA, IL6 and IL17A/F1). These findings will contribute to the understanding of how ZSS alleviates SD-induced anxiety, and provide a theoretical basis for the clinical application of ZSS.